It's mine! - Lionni, Leo, 1910-1999. (New York : Knopf : Distributed by Random House, 1986)
Three selfish frogs quarrel over who owns their pond and island, until a storm makes them value the benefits of sharing.
2.9
K-3
K-3
Wilson's Children
School Library Journal
Kirkus Review
Keywords: Selfishness -- Fiction; Sharing -- Fiction; Frogs -- Fiction; Frogs -- Fiction